1998
DOI: 10.7326/0003-4819-128-9-199805010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Mechanical Ventilation in the Weaning of Patients with Respiratory Failure Due to Chronic Obstructive Pulmonary Disease

Abstract: Noninvasive pressure support ventilation during weaning reduces weaning time, shortens the time in the intensive care unit, decreases the incidence of nosocomial pneumonia, and improves 60-day survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
270
8
43

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 591 publications
(340 citation statements)
references
References 28 publications
19
270
8
43
Order By: Relevance
“…They may continue invasive mechanical ventilation until patients can be extubated [5]. In selected cases, intensivists may extubate patients straight away and immediately institute noninvasive mechanical ventilation (NIV) [6,7]. In contrast, for patients recovering from hypoxemic respiratory failure intensivists have one choice: continue invasive mechanical ventilation until extubation [8].…”
mentioning
confidence: 99%
“…They may continue invasive mechanical ventilation until patients can be extubated [5]. In selected cases, intensivists may extubate patients straight away and immediately institute noninvasive mechanical ventilation (NIV) [6,7]. In contrast, for patients recovering from hypoxemic respiratory failure intensivists have one choice: continue invasive mechanical ventilation until extubation [8].…”
mentioning
confidence: 99%
“…There are two kinds of noninvasive assisted ventilation schemes: one is the use of noninvasive positive pressure ventilation immediately after the extubation (sequential invasive-noninvasive strategy); [21] the other is the use of noninvasive positive pressure ventilation when exacerbations of respiratory failure post extubation (noninvasive positive pressure ventilation as remedial strategy). [22] Many studies support the sequential invasive-noninvasive strategy, but researches on sequential invasive-noninvasive ventilation strategy mainly focused on the direct tracheal extubation of patients after their intubation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that extubation and weaning with noninvasive (by facemask), as opposed to invasive (by tracheal tube), ventilation can reduce VAP (28% vs. 0%) and mortality in suitable patients with respiratory failure secondary to chronic obstructive airways disease [87]. Survival rates at 60 days were significantly higher in the noninvasive group (92% vs. 72%); the excess deaths related to the complications of conventional mechanical ventilation, in particular pneumonia.…”
Section: Noninvasive Ventilationmentioning
confidence: 99%